Scrophulariae Radix-Atractylodes sinensis pair and metformin inhibit inflammation by modulating gut microbiota of high-fat diet/streptozotocin-induced diabetes in rats - Guo, Xiaoxia; Wang, Chong; Zhang, Ranran; Hao, Xuliang; Lv, Lei; Ni, Yan; Fan, Xiaohong; Zhang, Weiliang; Jiao, Yunhong; Song, Wei; Dong, Qi; Qi, Yuqi; et al. (Frontiers in Microbiology, 2022)
Type 2 diabetes mellitus (T2DM), a chronic metabolic disorder, causes severe impairment of patients' quality of life and has attracted global attention. Many studies have suggested the importance of the gut microbiota in the occurrence of T2DM. The Scrophulariae Radix and Atractylodes sinensis (XC) pair, recommended in traditional Chinese medicine (TCM), have been used for treating diabetes for many years. However, research on the role of the XC pair in modulating gut microbial communities is lacking, but it is important to elucidate the underlying mechanism. In this study, we detected bacterial communities by high-throughput 16S rRNA gene sequencing. The results showed that XC+MET reduced postprandial hyperglycemia and inflammatory response in diabetic rats more effectively than MET alone. The XC+MET treatment reshaped the intestinal microbial composition of diabetic rats. XC can help metformin regulate carbohydrate, amino acid, and lipid metabolism, particularly the insulin signaling pathway. This research would help elucidate potential mechanisms and the treatment methods.